Malicious Spam Distribution: A Routine Activities Approach. Issue 2 (1st February 2022) - Perkins, Robert C.; Howell, C. Jordan; Dodge, Cassandra E.; Burruss, George W.; Maimon, David
ABSTRACT: The distribution of malicious spam occurs in substantial numbers around the globe and can function as a precursor to serious forms of cybercrime. Yet to date, no known study has employed criminological theory to gain insight into the macro-correlates of malicious spam victimization. To address this gap in the literature, the current study utilizes data gathered from multiple sources to assess whether variables derived from routine activity theory are associated with malicious spam victimization at the country-level. Findings indicate that multiple measures of target suitability increase the amount of malicious spam a country receives. Specifically, corruption, political freedom, gross domestic product, and being an Asian nation are associated with an increase in malicious spam victimization. Capable guardianship, however, does not decrease the amount of malicious spam a country receives, and in some instances, is associated with an increase. Theoretical and policy implications are discussed.